2019
DOI: 10.48550/arxiv.1909.09584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gromov-Lawson codimension 2 obstruction to positive scalar curvature and the C*-index

Yosuke Kubota,
Thomas Schick

Abstract: Gromov and Lawson developed a codimension 2 index obstruction to positive scalar curvature for a closed spin manifold M , later refined by Hanke, Pape and Schick. Kubota has shown that also this obstruction can be obtained from the Rosenberg index of the ambient manifold M which takes values in the K-theory of the maximal C * -algebra of the fundamental group of M , using relative index constructions.In this note, we give a slightly simplified account of Kubota's work and remark that it also applies to the sig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The situation of Example 5.10 was previously studied by Hanke, Pape, and Schick [18]. Moreover, Kubota [23,24] showed that if X is closed, then it has non-vanishing Rosenberg index.…”
Section: We Mention Two Further Examplesmentioning
confidence: 91%
“…The situation of Example 5.10 was previously studied by Hanke, Pape, and Schick [18]. Moreover, Kubota [23,24] showed that if X is closed, then it has non-vanishing Rosenberg index.…”
Section: We Mention Two Further Examplesmentioning
confidence: 91%